POTENSI DISFUNGSI KETENTUAN PIDANA TENTANG PENGHINAAN TERHADAP ORANG MATI MENGGUNAKAN TEKNOLOGI INFORMASI - Widodo, Widodo; Utami, Wiwik (Jurnal Magister Hukum Perspektif, 2024)
The honor of deceased people is protected by the Indonesian Criminal Code so that if there is defamation against him, the perpetrator will be punished. However, if defamation is carried out using Information Technology, it is not necessarily punishable, because there are differences in the media used. The researchers concluded that article 27 (3) the Information and Electronic Transaction Act can be used to prosecute perpetrators, but it turns out there are multiple interpretations in the legal regulations and the contents of the Joint Decree (SKB) of the Chief of Indonesian Police, the Attorney General and the Minister of Communication and Information which have the potential to make this article dysfunctional. It is necessary to examine the existence of Article 27 (3) as a basis for investigating and prosecuting perpetrators of criminal acts of defamation of deceased people using Information Teccnology, and the normative weaknesses of the SKB editorial in number 3 letters a and g. The doctrinal research method with a statutory approach is used to examine these 2 problems. Legal materials in the form of Article 27 (3) and its explanation, SKB, and other legal materials were analysed using content analysis techniques. There is no conflict between the contents and the explanation of Article 27 (3), so that it can be used as a basis for investigating and prosecuting perpetrators of defamation of deceased people. The contents of the SKB have multiple interpretations, there is a conflict between the contents of the SKB and the Explanation of Article 27 (3) because in number 1 the SKB only refers to the provisions of Article 310 of the Indoensian Criminal Code, not to defamation as regulated by the Criminal Code. The existence of this SKB has the potential to cause dysfunction of Article 27 (3) which is now Article 27A of the Information and Electronic Transaction Act as the basis for processing criminal law against perpetrators of defamation of deceased people using Information Teccnology. There needs to be a change in the contents of the SKB or a material review of the SKB is needed at the Supreme Court so that it is easy to apply Article 27A. Keywords: dysfunction, crime, defamation, information technology, deceased people